THE EFFECT OF SCHOOL PRINCIPAL SUPERVISION AND ORGANIZATIONAL CLIMATE ON PRIMARY SCHOOL TEACHER PERFORMANCE - AGUSTIANI, Elvi; MULJONO, Hery; BUNYAMIN, Bunyamin (Journal of Education and Leadership in Education, 2024)
This research aims to investigate the influence of: 1) principal supervision on teacher performance, 2) organizational climate on teacher performance, 3) principal supervision on organizational climate. This research is quantitative research with a correlational design which aims to describe or describe whether there is an influence between two or more variables. The variables studied were principal supervision (X1), organizational climate (X2), and teacher performance (X3). The population of this study was 182 teachers with a sample size of 125 teachers determined using the Slovin formula with a trial sample size of 30 teachers. Data was collected using an instrument in the form of a questionnaire via Google Form Likert scale model and analyzed with descriptive statistics. To test the hypothesis, a multiple linear regression test was used which was calculated using SPSS 22. The research results show that: First, there is a positive and significant direct influence of principal supervision (X1) on teacher performance (X3). The significance value is 0.000 < 0.05 and t count is 6.542 ˃ t table 1.97960. The coefficient of determination 21.07%. Second, there is a positive and significant direct influence of organizational climate (X2) on teacher performance (X3). The significance value is 0.000 < 0.05 and t count is 62.005 ˃ t table 1.97960. The coefficient of determination 41.99%. Third, there is a positive and significant direct influence of principal supervision (X1) on organizational climate (X2). The significance value is 0.000<0.05 with the correlation coefficient is 0.653 and a coefficient of determination of 42.64%.